Tonalʹnostʹ razgovornogo teksta: tri sposoba opisaniâ - Matveeva, Tamara V. (Stylistyka, 1996)
The article is methodological in character. The author admits the possibility of analysing the text of conversational dialogical productions and offers to use the over-all descrip- . tion o f text categories. The category of the musical key makes it possible to show the combination of the description o f the field (which allows one to pick out the functiostylistical nucleus of the category), of speech-action (which determines the composition of the tactics and strategies of typical speech) and of genre (this category is examined as one of the parameters o f the categorial frame of genre).